Breastfeeding Practice Protect Children under Five Years Age form Stunting - Lina Anggaraeni Dwijayanti; Sayu Putu Sri Adnyani; Luh Ayu Purnami; Ni Ketut Ayu Wulandari (Indonesian Journal of Global Health Research, 2023)
Identification of risk factors stunting is important as prevention and early detection. However, breastfeeding initiation, early exposure to colostrum, exclusive breastfeeding, and duration of breastfeeding as a risk factor of stunting is still inconsistent. This study aimed to analyze the association of breastfeeding practice with stunting in children under five years of age. Observational study with a case-control design was conducted in Sawan, Buleleng District. A total of 48 cases and 48 controls were selected to participate in the study by using cluster sampling. Stunting data were obtained by direct measurements using microtoise and length boards, while variables related to breastfeeding and respondent characteristics variables were obtained by direct interviews using a questionnaire. All item questionnaire were valid (r count > r table (0,367)) and reliabel (cronbach’s alpha 0,741). Data were analyzed with chi-square, and multivariate analysis by using logistic regression. The multivariate analysis result showed that variables were associated with stunting among children under five years of age are exclusive breastfeeding (AOR:4.27; 95%CI: 1.663-10.945), and breastfeeding initiation (AOR:3.46;95% CI:1.304-9.176). here is a need to increase the coverage of early breastfeeding initiation and exclusive breastfeeding to prevent an increase in stunting prevalence.